Pharmacokinetics of a Single Oral Dose of the MEK1/2 Inhibitor Selumetinib in Subjects With End‐Stage Renal Disease or Varying Degrees of Hepatic Impairment Compared With Healthy Subjects. (26th December 2016) - Dymond, Angela W.; Martin, Paul; So, Karen; Huang, Yifan; Severin, Paul; Holmes, Victoria; Mariani, Gabriella; Marbury, Thomas
Abstract: Two phase I open‐label studies were conducted to investigate the pharmacokinetics (PK), safety, and tolerability of single oral doses of selumetinib in subjects with end‐stage renal disease (ESRD) undergoing hemodialysis and subjects with varying degrees of hepatic impairment; both studies included a matched control group comprised of healthy individuals. In the renal impairment study, subjects received single doses of selumetinib 50 mg; those with ESRD received selumetinib before and after dialysis (with a between‐treatment washout period of ≥7 days). In the hepatic impairment study, subjects received varying single doses of selumetinib (20‐50 mg) depending on liver dysfunction (mild, moderate, or severe as per Child‐Pugh classification). PK, safety, and tolerability data were collected from both studies. Overall, 24 subjects were included in the renal impairment study (ESRD, N = 12; healthy subjects, N = 12). Selumetinib exposure (AUC and Cmax ) was not increased in the ESRD group vs healthy subjects. Selumetinib exposure was lower when selumetinib was dosed before vs after dialysis, although individual exposure was variable. Overall, 32 subjects were included in the hepatic impairment study (mild, moderate, and severe impairment, N = 8 per group; healthy subjects, N = 8). Generally, dose‐normalized total selumetinib exposure was increased by 25% to 59% in subjects with moderate and severe hepatic impairment compared with healthy subjects. Increasing Child‐Pugh score, decreasing serum albumin, and increasing prothrombin time correlated with increasing unbound selumetinib exposure. In both studies, selumetinib was well tolerated with no new safety concerns. These studies will inform dose adjustment considerations in patients.